EFEKTIVITAS KEBIJAKAN SURAT KEPUTUSAN MENTERI HUKUM DAN HAM RI NOMOR M.HH-19.PK.01.04.04/2020 - Napitupulu, Agustinus F. I.; Puspitaningrum, Jayanti; Suwito, Suwito; Andrias, Maria Yeti; Aituru, Yulianus Payzon (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The basic right to life is a human right protected in the Indonesian constitution. In this case, residents of the assisted communities still have the right to life as part of their human rights so that the state is obliged to try to protect them from the dangers of the Covid-19 pandemic which threatens the location of prisons where assisted residents live. The implementation of the policy of the Decree of the Minister of Law and Human Rights of the Republic of Indonesia Number M.Hh-19.Pk.01.04.04/2020 has not been very effective because there are still prisoners and children who are returned to prisons or detention centers for returning to commit crimes. In the field of supervision, there are still shortcomings, namely that supervision only involves elements of the Bapas and the Prosecutor's Office which are limited.